A new species of Placotrochides Alcock, 1902 (Anthozoa: Scleractinia: Flabellidae) from the tropical Western Pacific, including the deepest record of the genus - Li, Yang; Cheng, Yu-Rong; Xu, Kuidong (Zootaxa, 2017)
A new species of azooxanthellate solitary Scleractinia, Placotrochides yapensis n. sp., is described from the foot of a seamount near the Yap Trench in the tropical Western Pacific at the water depth of 2,700–2,734 m. The specimens are assigned to the genus Placotrochides Alcock, 1902 on account of possessing a solitary corallum, a trabecular columella and the transverse division resulting in a free anthocyathus with a basal scar. The new species differs from its four congeners by (1) the larger corallum size (greater calicular diameter 15.2–15.7 mm, greater basal scar diameter 9.0–12.2 mm, and height 13.3–17.1 mm), (2) the larger edge angle (20–25°), (3) the arrangement of septa (S1–2>S3>S4), and (4) the number of septa (48). Until now, five species of Placotrochides have been known from deep waters and Placotrochides yapensis n. sp. is the deepest record of the genus.